OPFINDELSEN AF ALKOHOLISME - Orbe, Dan (Tidsskriftet Antropologi, 1998)
Dan Orbe: The Invention of Alcoholism All societies are known to use intoxicants, and alcohol is the most widely used substance of them all. However, no direct connection between the physical effects of alcohol on the human organism and the intoxicated behaviour of the users can be established. Instead, the cultural context of alcohol use seems to influence not only the intoxicated behaviour, but also the problems various societies experience with regard to alcohol. Likewise, the definitions and explanations of such problems appear to be relative to certain cultures and to certain periods of time. One such explanation regards the excessive use of alcohol as a disease which either develops as a result of the use of alcohol over a long period of time or as a combination of alcohol use and certain unknown - perhaps hereditary - factors in certain predisposed individuals. The article describes how the problematisation of excessive alcohol use through this type of explanations has developed since the late 18th century as part of a process in which natural science gradually redefined the understanding of human behaviour, and societal changes in North America and Europe created new moral and ethical standards